Identification key, checklist and new species of Loneura Navás (Psocodea: ‘Psocoptera’: Ptiloneuridae) from Brazil - Cutrim, Marcelo; Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2021)
Four Brazilian species of Loneura are described and assigned to infrageneric groups: L. digitiformis n. sp., L. manauara n. sp., and L. marinonii n. sp, to Loneura group I, and L. duckei n. sp. to Loneura group II. This genus now comprises 45 species, of which 8 (18%) are from Brazil. Of these species, 19 are known only from males, 4 known only from females, 21 are known from both sexes, with one species of unknown sex. The infrageneric classification is based on the number of hypandrium sclerites, either one or three, and is based on the 40 species for which males are known, with 20 species in Group I and 20 species in Group II. An identification key to species from Brazil based on male characters is provided, together with a checklist.